2003
DOI: 10.1016/s0006-3495(03)74787-0
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Study of ATP-Induced Changes in Na+/K+-ATPase from Duck Supraorbital Glands

Abstract: The Na+/K+-ATPase uses energy from the hydrolysis of ATP to pump Na+ ions out of and K+ ions into the cell. ATP-induced conformational changes in the protein have been examined in the Na+/K+-ATPase isolated from duck supraorbital salt glands using Fourier transform infrared spectroscopy. Both standard transmission and attenuated total internal reflection sample geometries have been employed. Under transmission conditions, enzyme at 75 mg/ml was incubated with dimethoxybenzoin-caged ATP. ATP was released by fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
1
9
2
Order By: Relevance
“…In this regard, Chetverin et al indicated that according to their results the enzyme working cycle lacks gross structure changes (85). On the other hand, Pratap et al, reporting an investigation related to ATP-induced conformational changes in Na + /K + -ATPase, indicated that from their FTIR results it is not possible to decide if these changes correspond to large changes localized in the cytoplasmic loop between the M4 and M5 transmembrane domains or a sum of smaller changes that occurred throughout the protein (86).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Chetverin et al indicated that according to their results the enzyme working cycle lacks gross structure changes (85). On the other hand, Pratap et al, reporting an investigation related to ATP-induced conformational changes in Na + /K + -ATPase, indicated that from their FTIR results it is not possible to decide if these changes correspond to large changes localized in the cytoplasmic loop between the M4 and M5 transmembrane domains or a sum of smaller changes that occurred throughout the protein (86).…”
Section: Discussionmentioning
confidence: 99%
“…Ca-ATPase and Na ⁄ K-ATPase have been extensively investigated by time-resolved FTIR absorbance difference spectroscopy using various nucleotides and nucleotide analogues [7][8][9][10][11][12][13]. These studies have suffered from the fact that the described mammalian proteins could only be purified from native tissue material.…”
mentioning
confidence: 99%
“…It is established that there is a two-side relationship between Na + /K + -ATP-ase activity and concentration of Na + and K + ions. In particular, Na + /K + -ATP-ase is the main enzyme regulating the concentration gradient of Na + and K + ions in intra-and extra-cellular areas; But mentioned ions, in turn, play the role of enzyme's regulators [1] [16].…”
Section: Resultsmentioning
confidence: 99%
“…Na + \K + -ATP-ase belongs to the transporter family of P-type ATP-ases [1]. It's known that the enzyme performs the signaling function in addition to the transport function [1] [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation